Hälsinglands inredningskultur - Nyström, Ingalill; Palmsköld, Anneli; Knutsson, Johan (Kriterium, 2021)
This anthology is a conclusion of the research results from a four-year VR project called Decorated Farmhouses of Hälsingland - a holistic study of a World Heritage (2014-2017). Decorative painted interiors and furniture as well as patterned interior textiles during 1700-1870 have been investigated with a combination of methods from both the humanities and the natural sciences. The purpose has been to obtain new and in-depth knowledge of paint, dyes and other raw materials and techniques used in the manufacture of artefacts and interiors in the farmhouses in this region. Through the study, an increased understanding of the local availability of paint material and the trade at that time has been obtained. In addition, detailed knowledge of the originators of the interiors has been generated. The project thus adds new knowledge for further investigation of cultural, social and economic contexts and conditions for the interior design culture that emerged and was formed in Hälsingland farms during the 18th and 19th centuries.